A Critique of Libet and Wegner’s Argument Against Free Will - Fosu-Blankson, Ferdinard; Inusah, Husein (Journal of NeuroPhilosophy, 2023)
The research of Benjamin Libet and Daniel Wegner are groundbreaking works in neuropsychology that make arguments against human freedom. However, Libet’s and Wegner’s arguments are marred with some philosophical inconsistencies including; misconceptions, logical errors, and causal fallacies which seems to emanate from the problem of subjecting the concept of free will to an empirical enquiry only. In this essay, it is argued that empirical enquiry alone limits the study of the role of consciousness and its involvement in decision-making. It is suggested that scientific assessment alone may not be exhaustive in the evaluation of the idea of free will considering the role of consciousness and the absence of causal evidence between the interactions of the mind and the brain.